(untitled) (EAAE Annual Conference Proceedings, 2023)
The role of architect in recovery process covers a wide horizon of different sectors and diverse topics. Lately,Turkiye has lived different crisis, including natural disasters, political and economic crisis with refugees’ waves from neighboring countries which suffered armed conflict. This required a shifting in mentality for the teaching and training of architecture students to comprehend and be prepared for their role in the post crisis recovery process.